Manejo y control de Agrotis ipsilon en el cultivo de maíz (Zea mays L.), en el barrio El Tejar, ciudad de Ibarra - Delgado Loor, Elsa Viviana (2019)
SUMARY This research work was carried out in the El Tejar neighborhood, Ibarra canton, in which it was identified that phytosanitary problems are the main cause, low yields and low quality of the cob that farmers face. To carry out this work, the following objectives were proposed: Identify the morphological characteristics of the plague insect called Agrotis ypsilon; Identify the damage caused and the symptomatology of the insect that attacks the crop and know the management carried out by the producers for the control of pests and diseases in the crop. The damage caused by the insect causes production costs to increase and low economic income, due to ignorance of the identification of the pests, a compilation of information was made on the main phytosanitary problems that attack these crops; This information was collected directly from the main source, in the same area and with the affected farmers, through surveys, interviews and field monitoring, identifying the main pests that affect this crop, especially the pulper. This plague is a larva that attacks at night, completely cut the corn stem, this damage is done in the initial stage in which it is very susceptible and weak, after the first month the plants become very hard and are no longer you attack The most important control is the application of chemical products, mainly Lorsban and Nuvacron, with a dose of 500 to 750 mm/gr and a frequency of eight days during the critical stage. It is very important to hold training events to improve crop productivity.